Forecasting mortality rates with Recurrent Neural Networks - Bravo, Jorge Miguel (2021)
Bravo, J. M. (2021). Forecasting mortality rates with Recurrent Neural Networks: A preliminary investigation using Portuguese data. In CAPSI 2021 Proceedings: 21ª Conferência da Associação Portuguesa de Sistemas de Informação, "Sociedade 5.0: Os desafios e as Oportunidades para os Sistemas de Informação".". [21th Portuguese Association of Information Systems Conference] (pp. 1-19). Associação Portuguesa de Sistemas de Informação. https://aisel.aisnet.org/capsi2021/7